Improving Teacher Performance through a Balanced Scorecard Learning Perspective at SDIT Aya Sophia Tangerang - Agus Siswadi; Jajat Sudrajat; Richad Dedi Syahbudin Afandi; Rudiyanto Dahlan; Imam Asrofi (Yayasan Aya Sophia Indonesia, 2025)
Improving teacher performance is a strategic agenda in facing the challenges of 21st century education, especially in Islamic-based basic education units. This study aims to analyze the application of the learning perspective in the Balanced Scorecard (BSC) framework as a strategy to improve teacher performance at SDIT Aya Sophia Tangerang. Using a qualitative-descriptive approach, data were collected through in-depth interviews, participatory observation, and documentation study of seven key informants directly involved in school management. The results show that HR capacity building, data-based work program planning, and implementation of ongoing training significantly improve teachers' professionalism, learning effectiveness, and stakeholder satisfaction. Learning indicator-based performance evaluation promotes a reflective and collaborative culture within the school. In addition, the integration of Islamic values with the strategic management approach resulted in synergy between academic achievement and character strengthening. This study recommends the application of BSC as an adaptive, measurable and contextualized internal quality management tool for integrated Islamic schools in Indonesia